'Safe' political discourse: Linguo-cultural and pragma-linguistic perspectives - Ludmila L. Baranova; Natalia L. Kriakina (Peoples' Friendship University of Russia (RUDN University), 2020)
The study seeks to identify the main tendencies in the use of politically correct language from the linguo-cultural and pragma-linguistic perspectives. The paper offers an overview of the ways in which political correctness is expressed in the British and American political discourse. The study is corpus-based; the contexts illustrating theoretical hypotheses are borrowed from three large-scale corpora of the corresponding variants of English (British National Corpus, Corpus of Contemporary American English, and Hong Kong Baptist University Corpus of Political Speeches). The study relies on the linguo-cultural and pragma-linguistic paradigm supplemented by discourse analysis. Research results indicate that British and American political discourse has both general and culture-specific features. Speakers from both the USA and the UK tend to refer to milestone events their audience is well-acquainted with. They use a wide array of general notions, as well as specific terms and set expressions depending on the impression they wish to make on their listeners. American politicians appear to be inclined towards using less formal lexis such as 'opposing the nation's enemies' and 'political rivals', whereas their British counterparts tend to choose more formal terms and expressions. Modern political discourse is characterised by continuity: it is inextricably connected with the previous stages in its development, while at the same time acquiring new peculiarities and taking new forms.